Where did people die from cardiovascular disease? Spatial inequalities in cardiovascular mortality in Belgium between 1890 and 2011 - Lise Bevernaegie; Isabelle Devos; Sylvie Gadeyne (Espace populations sociétés)
In the early 20th century, mortality due to cardiovascular disease (CVD) was relatively uncommon. Most Western countries only faced a huge increase in cardiovascular deaths during the second part of the 20th century only [Grimmeau et al., 2015]. In Belgium, the trajectory of CVD fatalities unfolded in this manner: from 4% of all deaths in 1850 to 9% in 1910, 29% in 1950 and 37% in 1995, followed by a decline from 36% in 2000 to 25% in 2019 [Devos, 2006; STATBEL, 2022]. In 2022, CVD ranks as the second largest cause of death in Belgium [STATBEL, 2022]. Regional differences were observed in the 1930s [Selleslags, 1938] and in the late 20th and early 21st century, with Wallonia being more strongly affected than Flanders, particularly for men [Gossiaux, 1983 ; Grimmeau et al., 2015 ; Kornitzer et al., 1979 ; Lemonnier, 1981 ; Renard, Tafforeau and Deboosere, 2015]. Despite these finding, analyses of long-term trends at the municipal level are lacking, as most CVD studies on spatial inequality in Belgium have focussed on larger spatial units such as provinces and districts, obscuring local disparities and hotspots. Yet, examining CVD mortality at a more localized level is essential for tracking the local effects on health inequalities [Asaria et al., 2012 ; Eggerickx, Sanderson and Vandeschrick, 2020]. This article fills this gap by describing the spatial disparities in CVD mortality at the municipal level from 1890 to 2011. Using unique aggregated data from death certificates and censuses, standard mortality ratios (SMRs), and percentages CVD deaths to total deaths are calculated and presented on maps. As such, this research offers, for the first time in Belgium, a description of the spatiotemporal disparities in CVD mortality. The findings elucidate that, during the early 20th century, no discernible regional patterns were evident at the municipal level in Belgium. However, starting in the 1970s, significant hotspots began to appear within the Walloon provinces. Notable disparities in CVD mortality between men and women are apparent at the national level, with a slightly higher mortality rate among women consistently observed across all years. Nevertheless, both sexes demonstrate similar spatial hotspots over time. Further research should explore the influence of environmental and socioeconomic factors on CVD mortality patterns at a local level.